Can trichomonas immunochromatographic test increase the validity and reliability of WHO syndromic algorithm for vaginal discharge as a screening tool for trichomoniasis? - Banneheke, H.; Fernandopulle, R.; Gunasekara, U.; Barua, A.; Fernando, N.; Wickremasinghe, R. (Annals of Tropical Medicine and Public Health, 2016)
Attached

Background: Trichomoniasis is a sexually transmitted parasitic infection. The World Health Organization (WHO) v rivocated flow charts for curable sexually transmitted infections (STIs) to improve the care. In this study, an attempt was made to evaluate the validity and reliability of WHO syndromic algorithm for vaginal discharge against trichomonas immunochromatographic test (ICT). Trichomonas ICT is a test with high validity, reliability, and feasibility. Objectives: The objective was to evaluate the validity and reliability of "WHO syndromic algorithm for vaginal discharge" against "trichomonas ICT" as a screening tool for trichomonas infection among women of reproductive age in the Western Province, Sri Lanka. Materials and Methods: This cross-sectional study was conducted in sexually transmitted disease clinics, well woman clinics, gynecology clinics, and institutional health clinics in the Western Province, Sri Lanka. We enrolled 100 women in die age group of 15-45 years using the stratified random sampling method. They were interviewed and examined and the specimens were collected to identify trichomoniasis by culture and ICT. Two-stage analyses were done to evaluate the performance of the WHO algorithm against Trichomonas ICT. Results: In a two-stage analysis, the specificity of syndromic algorithm improved from 80.9% to 94.4% while false positive rate reduced from 19.1% to 5.6%. The net effect of specificity was 98.7% while the false positive rate was 1.3%. Conclusion: The validity and reliability of WHO syndromic algorithm as a diagnostic tool for trichomoniasis can be improved by adding trichomonas ICT
Keywords: Vaginal discharge; validity